Status of soil available nickel (Ni) in different districts of eastern Uttar Pradesh, India - SINGH, SATISH KUMAR; PATRA, ABHIK (The Indian Journal of Agricultural Sciences, 2020)
Limited information is available regarding status of available Ni in Indian soil and almost no literatures available on Ni deficient soils. Hence, the present investigation was undertaken to generate database on Ni content in soil and identifying the potential Ni deficit areas. Plant available Ni in different districts soils was assessed by analyzing 526 surface soil samples from Varanasi, 684 from Mirzapur, 523 from Sant Ravidas Nagar and 558 from Chandauli district. The soil samples were analysed for soil reaction (pH), EC, organic carbon and DTPA extractable Ni. All the blocks of Varanasi were high in Ni and its content ranged from 0.03–20.88 mg kg-1. In Mirzapur district, overall 7.16% soil samples were Ni deficit, however at block level, highest deficiency was observed in Sikhar (31.67%) followed by Kon (27.78%) and Majhawa (24.32%). All the blocks of Sant Ravidas Nagar were high in nutrient index rating with variation in Ni content from 0.01–3.31 mg kg-1. Among the four districts, lowest number of Ni deficient soils (1.79 %) were found in Chandauli district with high nutrient index rating. While Mirzapur district had highest Ni deficit soil (7.16%) followed by Sant Ravidas Nagar (4.02%), however, potential threat of Ni deficiency was the highest in Sant Ravidas Nagar (22%) followed by Mirzapur (19%).